A study on improvement of chain to belt material conveying for mobile conveyor - Mohammad Zubair B Mohd Arifin (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
The scope of this study are to distinguish between existing mobile chain conveyor with belt conveyor in order to improve the effciencies of the dynamic resolving of palm oil fruit from farm to dumping area. These two conveyors which is chain type conveyor and belt type conveyor will be done a testing on speed and vibration that related between these two reponse to achieve the real time data analysis. Vibration data result that was obtained by using accelerometer gauge. Than, Lab View Signal Express software was used to convert output from accelerometer to necessary parameter required to compared this data to calculated by using speed calculation.